Racial disparities in clinical presentation, surgical procedures, and hospital outcomes among patients with hepatocellular carcinoma in the United States. (February 2023) - Chikovsky, Liza; Kutuk, Tugce; Rubens, Muni; Balda, Amber N.; Appel, Haley; Chuong, Michael D.; Kaiser, Adeel; Hall, Matthew D.; Contreras, Jessika; Mehta, Minesh P.; Kotecha, Rupesh
Abstract: Background: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths in the United States (US), with substantial disparities observed in cancer incidence and survival among racial groups. This study provides analyses on race and ethnicity disparities for patients with HCC. Methods: This is a cross-sectional analysis of data from the National Inpatient Sample (NIS) between 2011 and 2016, utilizing the STROBE guidelines. Multivariate logistic regression analyses were used to examine the risk-adjusted associations between race and pre-treatment clinical presentation, surgical procedure allocation, and post-treatment hospital outcomes. All clinical parameters were identified using ICD-9-CM and ICD-10-CM diagnosis and procedure codes. Results: 83, 876 weighted HCC hospitalizations were reported during the study period. Patient demographics were divided according to NIS racial/ethnic categorization, which includes Caucasian (57.3%), African American (16.9%), Hispanic (15.7%), Asian or Pacific Islanders (9.3%), and Native American (0.8%). Association between greater odds of hospitalization and Elixhauser Comorbidity Index > 4 was significantly higher among Native Americans (aOR=1.79; 95% CI: 1.23–2.73), African Americans (aOR=1.24; 95% CI: 1.12–1.38), and Hispanics (aOR=1.11; 95% CI, 1.01–1.24). Risk-adjusted association between race and receipt of surgical procedures demonstrated that the odds of having surgery was significantly lower for African Americans (aOR=0.64; 95% CI: 0.55–0.73) and Hispanics (aOR=0.70; 95% CI: 0.59–0.82), while significantly higher for Asians/Pacific Islanders (aOR=1.36; 95% CI: 1.28–1.63). Post-operative complications were significantly lower for African Americans (aOR=0.68; 95% CI: 0.55–0.86) while the odds of in-hospital mortality were significantly higher for African Americans (aOR=1.28; 95% CI: 1.11–1.49) and Asians/Pacific Islanders (aOR=1.26; 95% CI: 1.13–1.62). Conclusions: After controlling for potential confounders, there were significant racial disparities in pre-treatment presentations, surgical procedure allocations, and post-treatment outcomes among patients with HCC. Further studies are needed to determine the underlying factors for these disparities to develop targeted interventions to reduce these disparities of care. Highlights: This study provides analyses on race and ethnicity disparities for patients with HCC. There were racial disparities in pre-treatment presentations, surgical procedure allocations, and post-treatment outcomes. Caucasians were the least likely to have pre-treatment comorbid conditions. African Americans, Native Americans, and Hispanics were less likely to receive surgical treatment. African Americans were less likely to develop post-operative complications and paradoxically had higher in-hospital mortality.